2016
DOI: 10.1007/s40279-016-0525-x
|View full text |Cite
|
Sign up to set email alerts
|

Co-ingestion of Nutritional Ergogenic Aids and High-Intensity Exercise Performance

Abstract: Many sports involve repeated bouts of high-intensity exercise. High-intensity exercise is compromised, however, by the early onset of exercise-induced fatigue. Metabolic by-products, ion dysbalance and amount of phosphocreatine are considered the main peripheral causes of fatigue during high-intensity exercise. Intake of nutritional ergogenic aids is commonplace to enhance performance of high-intensity exercise by offsetting the potential mechanisms of fatigue. Creatine, probably one of the best known nutritio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 81 publications
2
29
0
2
Order By: Relevance
“…Our findings lend support to an ever-growing thought according to which co-supplementation of multiple ingredients may not exactly confer greater benefit than isolated supplementation [17]. For example, Mero et al [18] demonstrated that, while sodium bicarbonate significantly reduced the time taken to complete repeated maximal swims compared to placebo, there was no additional benefit from co-ingestion of beta-alanine, another supplement which acts as a buffer, similar to sodium bicarbonate.…”
Section: Discussionsupporting
confidence: 73%
“…Our findings lend support to an ever-growing thought according to which co-supplementation of multiple ingredients may not exactly confer greater benefit than isolated supplementation [17]. For example, Mero et al [18] demonstrated that, while sodium bicarbonate significantly reduced the time taken to complete repeated maximal swims compared to placebo, there was no additional benefit from co-ingestion of beta-alanine, another supplement which acts as a buffer, similar to sodium bicarbonate.…”
Section: Discussionsupporting
confidence: 73%
“…Furthermore, responses to sodium bicarbonate appear subject to both intra- [31] and inter- [64] individual variability, at least in untrained participants. Although the performance effects of co-ingesting sodium bicarbonate and βalanine are unclear [65], several studies have investigated the effects of combined supplementation on training adaptations [66][67][68]. While a 4-wk loading period of β-alanine supplementation is typically used when studying co-ingestion, in all but one study [61] participant training sessions were not monitored.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement, our results allow us to conclude that BA is also an effective nutritional strategy to improve judo-related performance. Although studies on the combination of different buffering agents exist, 31 future studies are warranted to examine which one of these interventions may elicit the greatest improvement in judo performance, and, more importantly, whether their combination would have additive ergogenic properties.…”
Section: Discussionmentioning
confidence: 99%